Instantaneous and Cumulative Influences of Competition on Impulsive Choices in Domestic Chicks - Amita, Hidetoshi; Matsushima, Toshiya (Frontiers in Neuroscience, 2011)
This study examined instantaneous and cumulative effects of competitive interactions on impulsiveness in the inter-temporal choices in domestic chicks. Chicks were trained to peck colored beads to gain delayed food rewards (1 or 6 grains of millet delivered after a delay ranging between 0–4.5 s), and were tested in binary choices between a small-short delay option (SS) and a large-long delay alternative (LL). To examine whether competitive foraging instantaneously changes impulsiveness, we intraindividually compared choices between two consecutive tests in different contexts, one with competitors and another without. We found that (1) the number of the choice of LL was not influenced by competition in the tests, but (2) the operant peck latency was shortened by competition, suggesting a socially enhanced incentive for food. To further examine the lasting changes, two groups of chicks were consecutively trained and tested daily for 2 weeks according to a “behavioral titration” procedure, one with competitors and another without. Inter-group comparisons of the choices revealed that (3) choice impulsiveness gradually decreased along development, while (4) the chicks trained in competition maintained a higher level of impulsiveness. These results suggest that competitive foraging causes impulsive choices not by direct/contextual modification. Causal link between the instantaneous enhancement of incentive and the gradual effects on impulsivity remains to be examined. Some (yet unspecified) factors may be indirectly involved.